2006
DOI: 10.1007/s10517-006-0323-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delta sleep-inducing peptide on pre-and postsynaptic glutamate and postsynaptic GABA receptors in neurons of the cortex, hippocampus, and cerebellum in rats

Abstract: We studied the effect of delta sleep-inducing peptide on GABA receptors of hippocampal and cerebellar neurons in rats. It was shown that delta sleep-inducing peptide considerably and dose-dependently potentiates GABA-activated currents in these neurons and blocks NMDA-activated potentiation in cortical and hippocampal neurons. The peptide modulates activity of presynaptic NMDA receptors, which is seen from changes in (45)Ca(2+) uptake into synaptosomes of the brain cortex after uptake stimulation with glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…Another study has reported the ability of DSIP to block presynaptic NMDA receptors in the culture of neuronal cells of the rat cerebral cortex, as well as to reduce glutamate-or NMDA-stimulated uptake of Ca 2+ into synaptosomes [16]. An antihypoxic effect has been shown for DSIP in vitro, where it activated oxidative phosphorylation and increased the resistance of brain neurons to hypoxia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported the ability of DSIP to block presynaptic NMDA receptors in the culture of neuronal cells of the rat cerebral cortex, as well as to reduce glutamate-or NMDA-stimulated uptake of Ca 2+ into synaptosomes [16]. An antihypoxic effect has been shown for DSIP in vitro, where it activated oxidative phosphorylation and increased the resistance of brain neurons to hypoxia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Sudakov and colleagues showed that DSIP-caused activation of neurons at the sensorimotor cortex, dorsal hippocampus, ventral thalamic nuclei, and lateral hypothalamus could be explained by its action on NMDA receptors of these structures [ 50 ]. Grigor’ev et al showed that DSIP potentiated GABA-activated currents in hippocampal and cerebellar neurons and blocked NMDA-activated potentiation in cortical and hippocampal neurons [ 51 ]. There are available data that DSIP improves mitochondrial respiratory activity.…”
Section: Discussionmentioning
confidence: 99%
“…DSIP optimizes the excitation/inhibition relationship [36]. Namely, it potentiates GABA-activated currents in the hippocampal and cerebellar neurons in rats [37], which could be one of the major mechanisms of action in the model of lindane-induced seizures. On the other hand, Shandra et al [18] believe that the neuroprotective role of DSIP on NMDA receptors functions through the reduction of excitatory amino-acids and decrease of Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%